SOSIALISASI PENGELOLAAN LINGKUNGAN HIDUP PADA PENAMBANGAN BATUAN DI DESA WAESALA KECAMATAN HUAMUAL BELAKANG KABUPATEN SERAM BAGIAN BARAT - Ririmase, Pieter M; Makaruku, Marlita H (HIRONO : Jurnal Pengabdian Masyarakat, 2023)
Environmental and occupational safety issues in the mining business have always been the most important issues. The main problems that arise in ex-mining areas include environmental changes, which include chemical changes, physical changes and biological changes. Waesala Village within the scope of mining management is important and strategic because it has quite large potential for mining materials, especially rock-type minerals to support ever-increasing development. The purpose of this community service activity is to increase the knowledge of the people of Waesala Village in carrying out good environmental management at rock mining sites. This community service activity is carried out through the following stages: preparation, socialization, and activity evaluation. The results obtained from the implementation of this PKM activity are that there has been a very significant change in community knowledge about environmental management in mining areas after the implementation of community service activities.